Animal Assisted Therapy is an effort to reduce symptoms of violent behavior in patients with mental disorders - Nurbiyati, Tati; Pawestri, Pawestri; Dewi, Lily Kusuma; Arivani, Arum Lia; Indira, Eugene (South East Asia Nursing Research, 2023)
Violent behavior is a situation in which a person performs an action that can physically harm himself, others, and the environment. The risk of violent behavior is an angry response that is expressed by making threats or injuring oneself or others. Animal-assisted therapy with betta fish is a therapy to reduce anxiety behavior towards uncomplicated violent behavior with the principles of distraction and relaxation resulting from the interaction of therapy animals. The study aimed to determine the effect of animal-assisted therapy on reducing signs of violent behavior in patients with mental disorders. Research Methods Quasi-experimental research design with a one-group pretest and posttest design approach. Identification of respondents who fit the criteria, namely someone who experiences violent behavior in patients with mental disorders. Research Results Data analysis obtained an α-Symp Sig value of 0.004 <0.05, so there is an effect of animal assistance therapy on reducing symptoms of violent behavior in patients with mental disorders. The process of interaction with animal therapy can reduce the stimulus symptoms of violent behavior. Patients can control themselves by forming more positive behaviors such as reducing anger, appearing to have decreased tension, blood pressure does not increase. Conclusion There is an effect of animal-assisted therapy on reducing signs of symptoms of violent behavior in patients with mental disorders. Animal-assisted therapy suggestions can be used for violent behavior in mental patients